Productivity, water use and climate resilience of alternative cocoa cultivation systems - Abdulai, I. (Georg-August-Universität Göttingen, 2017)
Global demand for cocoa beans is projected to keep rising while future production is likely to be limited by climate variability and change. Over 70% of the global cocoa supply comes from West Africa, a region expected to be greatly affected by climate change and extreme droughts. Cocoa production in West Africa needs to be adapted to more marginal and extreme climatic conditions, mainly drought, to sustain production and avoid further deforestation of the remaining rainforest for its cultivation. In addition to the climate change effect, current yields are low due to management inefficiencies and soil limitations. Empirical data from cocoa agroforestry system studies are limited compared to those of other perennial crops such as coffee. In addition, the promotion of cocoa agroforestry as a sustainable production system is often based on anecdotes and should therefore be investigated further. There is still a huge knowledge gap on which shade tree species improve and sustain productivity, ecosystem functions (such as increase in flora and fauna diversity), and which are suitable for marginal climates with limited water supply. Studies on the effects of climatic variations on cocoa plant productivity across different regions are lacking although there is a general consensus on the requirement of developing climate change adaption options based on a sound scientific basis for the various regions. As a contribution towards bridging this research gap and help address current and future cocoa production challenges, for this thesis several studies were performed in Ghana, the second largest and best quality cocoa producing nation: Productivity of different cocoa cultivation systems was studied at three regions along a climatic gradient (from 2014 to 2016). Climate resilience of different cocoa cultivation systems was further investigated in the marginal regions through water use experiments over periods of wet, dry and extremely dry. Overall hypotheses of the thesis were that (i) climatic region does influence cocoa productivity, and (ii) agroforestry increases resilience of cocoa plants to marginal and extreme climatic conditions.